2016
DOI: 10.1002/poc.3638
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of 3,5‐diphenylisoxazole in argon matrices

Abstract: Broadband irradiation of 3,5‐diphenylisoxazole 1 in an argon matrix results in formation of azirine 3. Further irradiation of the matrix reduces the amount of azirine 3 with concurrent formation of ylide 4. Thus, it is theorized that the conversion of isoxazole 1 to azirine 3 goes through a triplet vinylnitrene 2 that does not intersystem cross to ketenimine 6. Hence, the reactivity of triplet vinylnitrene 2 is different from similar vinylnitrene intermediates with α‐methyl substituents that intersystem cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Species 2 a and 2 b (primary photoproducts of 1 a and 1 b , respectively) [32] are readily identified as 3‐hydroxy‐2‐formyl‐2 H ‐azirine and 3‐amino‐2‐formyl‐2 H‐ azirine, respectively [characteristic IR bands (argon matrix): 1818 [ν(C=N)] and 1733 [ν(C=O)] cm −1 for 2 a ; 1827 [ν(C=N)] and 1727 [ν(C=O)] cm −1 for 2 b ]. This assignment is supported by the previous IR spectral characterization reported for these molecules, [33] and is also consistent with the reported formation of 2 H ‐azirines as primary photoproducts in studies with other matrix‐isolated isoxazoles [13,34,35] . Subsequent irradiations were performed using longer wavelenghts where the isoxazole precursors 1 a and 1 b do not absorb.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Species 2 a and 2 b (primary photoproducts of 1 a and 1 b , respectively) [32] are readily identified as 3‐hydroxy‐2‐formyl‐2 H ‐azirine and 3‐amino‐2‐formyl‐2 H‐ azirine, respectively [characteristic IR bands (argon matrix): 1818 [ν(C=N)] and 1733 [ν(C=O)] cm −1 for 2 a ; 1827 [ν(C=N)] and 1727 [ν(C=O)] cm −1 for 2 b ]. This assignment is supported by the previous IR spectral characterization reported for these molecules, [33] and is also consistent with the reported formation of 2 H ‐azirines as primary photoproducts in studies with other matrix‐isolated isoxazoles [13,34,35] . Subsequent irradiations were performed using longer wavelenghts where the isoxazole precursors 1 a and 1 b do not absorb.…”
Section: Resultssupporting
confidence: 89%
“…This assignment is supported by the previous IR spectral characterization reported for these molecules, [33] and is also consistent with the reported formation of 2H-azirines as primary photoproducts in studies with other matrix-isolated isoxazoles. [13,34,35] Subsequent irradiations were performed using longer wavelenghts where the isoxazole precursors 1 a and 1 b do not absorb. It was observed that species 3 a and 3 b can be selectively converted to 4 a and 4 b, respectively, facilitating their unambiguous identification.…”
Section: Generation and Ir Spectral Characterization Of 3-hydroxy And...mentioning
confidence: 99%
“…The reaction proceeds via (i) a photochemical rearrangement of isoxazoles 1 to azirines 2 , (ii) a cobalt­(II)-catalyzed condensation reaction forming pyrroles 3 , and (iii) a [6π] photocyclization yielding the cycloheptadienones 4 . Curiously, only the trans product was observed for the phenyl derivative 4a , whereas cis / trans mixtures were obtained for furanyl and thienyl compounds 4b,c , an experimental finding that could not be rationalized at that time.…”
Section: Introductionmentioning
confidence: 99%
“…Professor Anna Gudmundsdottir and coworkers find the photochemical transformation of 3,5‐diphenylisoxazole to an azirine in argon. Further irradiation was found to produce the corresponding ylide in the low‐temperature matrix conditions. The formation of the azirine from the isoxazole is proposed to occur via a triplet nitrene intermediate, which is confirmed by theoretical calculations.…”
mentioning
confidence: 99%